The Effect of Profitability and Liquidity on Firm Value in Sub Manufacturing Companies Animal Feed Sector 2016-2020 - Rina Aulia Sari; Fanlia Prima Jaya (PT. Hanken SUkses Jaya, 2022)
This study aims to determine the effect of Profitability and Liquidity on Firm Value. The independent variables (X) studied are Profitability (X1) and Liquidity (X2) with the dependent variable (Y) being Firm Value (Y). The population used in this research is the Animal Feed Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange as many as 4 companies during 2016-2020. The sample selection used a purposive sampling technique which produced a sample of 20 samples. The data analysis technique used in this study is multiple linear regression analysis. The tests used are the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Hypothesis testing using the coefficient of determination, partial test (t), and simultaneous test (F). Based on the test results, it can be concluded that profitability has a significant effect on firm value, liquidity has no significant effect on firm value, profitability and liquidity simultaneously have a significant effect on firm value in manufacturing companies in the animal feed sub-sector in 2016-2020. Researchers provide advice to companies to continue to improve and improve financial performance to be able to increase the company's ability to generate value for the company so that it is more efficient and effective. Suggestions for investors, namely investors before deciding to invest in a company should pay attention to the level of performance of a company and consider other factors that affect the value of the company. And for other researchers it is suggested to use other variables that affect firm value.